Concentrations of total mercury and methylmercury in red snow crabs (Chionoecetes japonicus) caught off the coast of Japan. (August 2019) - Kakimoto, Sachiko; Yoshimitsu, Masato; Akutsu, Kazuhiko; Kiyota, Kyohei; Fujiwara, Takuya; Watanabe, Takahiro; Kajimura, Keiji; Yamano, Tetsuo
Abstract: The total mercury (T-Hg) and methylmercury (MeHg) concentrations in red snow crabs ( Chionoecetes japonicus ) caught off the coast of Japan were analyzed. The T-Hg concentration ranged from 0.03 to 0.56 mg/kg (mean: 0.21 mg/kg) in the raw muscle, and 0.02 to 0.74 mg/kg (mean: 0.27 mg/kg) in the boiled muscle. The MeHg concentration ranged from 0.04 to 0.54 mg/kg (mean: 0.20 mg/kg) in the raw muscle. The mean ratio of MeHg to T-Hg was 0.88. The crab body weight was found to significantly correlate with the concentrations of T-Hg (r = 0.488) and MeHg (r = 0.490) (p ≤ 0.01). For the general population in Japan, the intake of MeHg from eating red snow crab was estimated to be lower than 0.013 mg/week, which was less than one-sixth of the tolerable MeHg intake (0.08 mg/week). Highlights: T-Hg and MeHg in red snow crabs caught off the coast of Japan were analyzed. The validity of analytical methods of T-Hg and MeHg was also confirmed. Hg was found to be mainly accumulated in the form of MeHg. The concentration of T-Hg in red snow crabs is about the same as for other crabs. Estimated MeHg intake from these crabs in typical Japanese diet is considered safe.